2023
DOI: 10.3390/microorganisms11020379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Virulence, and Antibiotics Gene Profiles in Lactococcus garvieae Isolated from Cows with Clinical Mastitis in China

Abstract: Lactococcus garvieae (L. garvieae) is a pathogenic gram-positive, catalase-negative (GPCN) bacterium that causes bovine mastitis. A total of 49 L. garvieae isolates were identified from 1441 clinical mastitis (CM) samples. The pathogenic effects of L. garvieae were studied with two infection models: bovine mammary epithelial cells cultured in vitro and murine mammary infections in vivo. The overall farm prevalence was 15.5% (13/84 farms in 9/19 provinces) and sample prevalence was 3.40% (49/1441). Post-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The NLRP3 inflammasome plays a crucial role in the host's defense against bacterial infections [62], and is indispensable for L. garvieae in inducing inflammation and pyroptosis in MAC-T cells. Previous studies indicated the involvement of L. garvieae in mastitis development in cows [39]. However, there remains a lack of understanding regarding the molecular mechanisms by which L. garvieae induces mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLRP3 inflammasome plays a crucial role in the host's defense against bacterial infections [62], and is indispensable for L. garvieae in inducing inflammation and pyroptosis in MAC-T cells. Previous studies indicated the involvement of L. garvieae in mastitis development in cows [39]. However, there remains a lack of understanding regarding the molecular mechanisms by which L. garvieae induces mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…The two bacterial strains of L. garvieae LG41 and LG47 were stored at a temperature of -20°C in our laboratory before they were used for the study. The bacterial collection procedure was previously published, and more details on it can be found there [39]. The preserved bacterial strains were propagated in Sheep blood agar and brain heart infusion (BHI) (Qingdao Haibo Biotechnology Co., Ltd.).…”
Section: Bacterial Culture Of Lactococcus Garvieaementioning
confidence: 99%
“…The capsules present in L. garvieae are not only considered important virulence factors but are also collectively considered a defining characteristic of their serotype and phenotype classification (Salighehzadeh et al, 2020). The capsule may also play a protective role against host immune responses, antimicrobial agents, and environmental stressors (Voelz & May, 2010) in L. garvieae (Xie et al, 2023). Previously, it was believed that pathogenic L. garvieae isolates possessed capsules (KG−/agglutinating), whereas non‐capsulated isolates (KG+/non‐agglutinating) were non‐pathogenic (Barnes & Ellis, 2004; Ooyama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…garvieae (Xie et al, 2023). Previously, it was believed that pathogenic L. garvieae isolates possessed capsules (KG−/agglutinating), whereas non-capsulated isolates (KG+/non-agglutinating) were non-pathogenic (Barnes & Ellis, 2004;Ooyama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation